2021
DOI: 10.1186/s40842-021-00117-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between depression and risk of metabolic syndrome: a meta‐analysis of observational studies

Abstract: Introduction The link between metabolic syndrome and depression has always been controversial. Different studies that have examined the relationship between metabolic syndrome and depression have reported different results. Therefore, the goal of the present study was to examine the association between depression and MetS by meta-analysis. Methods Embase, Scopus, PubMed, and ISI were searched for publications in English from January 1990 to Februar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 66 publications
3
41
0
3
Order By: Relevance
“…Epidemiological data have been consistently proposed that depression was positively correlated with MetS risk [ 20 , 49 , 50 ]. Several meta-analyses of cohort studies suggested that depression was an independent risk factor for MetS, which agrees with our results [ 24 , 25 ]. As to the reverse direction, observational studies on the effect of MetS on depression risk were inconclusive.…”
Section: Discussionsupporting
confidence: 93%
“…Epidemiological data have been consistently proposed that depression was positively correlated with MetS risk [ 20 , 49 , 50 ]. Several meta-analyses of cohort studies suggested that depression was an independent risk factor for MetS, which agrees with our results [ 24 , 25 ]. As to the reverse direction, observational studies on the effect of MetS on depression risk were inconclusive.…”
Section: Discussionsupporting
confidence: 93%
“…It is not surprising that lower total serum bilirubin levels were proposed as a risk factor of vulnerability for different neurological and psychiatric disorders, including MDD [ 19 ]. Similarly, in light of the association between obesity and inflammation, metabolic syndrome and related biomarkers (e.g., dysregulated cortisol release) were hypothesized to be related to TRD [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Major depressive disorder (MDD) is associated with excess mortality ( 1 , 2 ). This appears to be in part mediated by an increased lifetime risk for obesity-related comorbidities, including cardiovascular disease (CVD), stroke, and type 2 diabetes mellitus ( 2 4 ). Overall, the association of cardiometabolic disorders and depression appears bidirectional as has been shown for obesity ( 5 ), metabolic syndrome (MetS) ( 6 ), type 2 diabetes ( 7 ), and CVD ( 8 ).…”
Section: Depression and Cardiometabolic Disordersmentioning
confidence: 99%